2008
DOI: 10.1100/tsw.2008.100
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activity of Aldonamides andN-Acyl-Diamine Derivatives

Abstract: A number of lipophilic N-acyl-diamines and aldonamides have been synthesized and tested for their in vitro antiproliferative activity against Leishmania amazonensis and L. chagasi. Ribonamides, having one amino group, displayed good to moderate inhibition of parasite growth. The best result was obtained for compounds 10 and 15 with IC50 against L. chagasi below 5 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, all therapies have some limitations as several toxic effects and unaffordable cost (5,6). In a previous study, we have shown that lipophilic diamine derivatives have proved inhibitory effects in Leishmania (7,8). So, the aim of this study was to evaluate in vitro some lipidic amino alcohols against different species of Leishmania .…”
Section: Values Of Ic50 (μM) For the Activity Of The Compounds Againmentioning
confidence: 99%
“…Nevertheless, all therapies have some limitations as several toxic effects and unaffordable cost (5,6). In a previous study, we have shown that lipophilic diamine derivatives have proved inhibitory effects in Leishmania (7,8). So, the aim of this study was to evaluate in vitro some lipidic amino alcohols against different species of Leishmania .…”
Section: Values Of Ic50 (μM) For the Activity Of The Compounds Againmentioning
confidence: 99%
“…Additionally, due to the hydrophobic nature of imidazolidines, they were employed as ethylenediamine carriers. Recently, various derivatives of polyamines with antiparasitic activity have been introduced [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the chemotherapy against Chagas disease has been based mainly on nifurtimox and benznidazole, which is associated with limited efficacy, long‐term administration, and several side‐effects . In previous studies, we have shown that polyamine derivatives display inhibitory effects against several species of Leishmania , Trichomonas vaginalis , Trypanosoma cruzi , and Plasmodium berghei , providing evidence that lipophilic diamines can be considered important leading molecules for developing new antiparasitic drugs. Currently, we present the preparation and biological in vitro activity evaluation for one 1,2‐ethanediamine derivative, eight 1,4‐butanediamine derivatives, and eight 1,6‐hexanediamine derivatives against T. cruzi , L. braziliensis and L. chagasi to complement earlier results and contribute to the development of an attractive antiparasite molecule derived from constitutive polyamines.…”
mentioning
confidence: 99%